Efficacy of a combination of non-drug therapies in patients with non-dementia vascular cognitive impairment - M. S. Novikova; V. V. Zakharov; N. V. Vakhnina (Неврология, нейропсихиатрия, психосоматика, 2023)
Objective: to study the effectiveness of a combination of non-drug methods in the treatment of non-dementia cognitive impairment of vascular etiology.Material and methods. The study involved 60 patients with moderate cognitive impairment of vascular etiology. The patients were divided into two groups: group 1 (n=30, mean age 63.7±8.8 years) received a combination of non-drug methods in the form of cognitive training, physical activity and meal planning for 1 month; patients of the 2nd group (n=30, mean age 64.2±10.7 years) were once informed about the advisability of a healthy diet and maintenance of mental and physical activity. Neuropsychological testing was done at the inclusion stage of the study, immediately after 1 month course of treatment, 6 months and a year after the start of the study. There were no significant differences between the groups in terms of cognitive functions at baseline.Results. After a month of treatment, in the 1st group the results of neuropsychological testing significantly (p<0.05) improved compared to the first visit: Montreal Cognitive Function Assessment Scale (MoCA-test) – from 22.5±2.4 to 23.7±2.8, Trail making test part A – from 56.9±20.1, up to 49.3±21.7; Trail making test part B – from 116.8±47.8 to 93.5±36.3; the Digit Symbol Substitution test (DSST) scores increased from 26.6±9.0 to 28.8±9.0. Categorical and literal fluency increased from 14.9±4.1 to 16.5±4.6 and from 10.0±1.7 to 11.6±1.9, respectively. In the 2nd group, 1 month after the start of the study, there were no significant differences from the baseline in neuropsychological tests. Differences between the groups at the second visit were statistically significant (p<0.05) according to the MoCA test, Trail making tests (parts A, B), DSST, and association tests. Significant differences between groups persisted during the first 6 months, but disappeared after 12 months of follow-up.Conclusion. Multimodal non-drug therapy in patients with moderate cognitive impairment of vascular etiology improves the main cognitive parameters.